Mapping of CaM, S100A1 and PIP2-Binding Epitopes in the Intracellular N- and C-Termini of TRPM4 - Bousova, Kristyna; Barvik, Ivan; Herman, Petr; Hofbauerová, Kateřina; Monincova, Lenka; Majer, Pavel; Zouharova, Monika; Vetyskova, Veronika; Postulkova, Klara; Vondrasek, Jiri (International journal of molecular sciences, 2020)
Molecular determinants of the binding of various endogenous modulators to transient receptor potential (TRP) channels are crucial for the understanding of necessary cellular pathways, as well as new paths for rational drug designs. The aim of this study was to characterise interactions between the TRP cation channel subfamily melastatin member 4 (TRPM4) and endogenous intracellular modulators-calcium-binding proteins (calmodulin (CaM) and S100A1) and phosphatidylinositol 4, 5-bisphosphate (PIP2). We have found binding epitopes at the N- and C-termini of TRPM4 shared by CaM, S100A1 and PIP2. The binding affinities of short peptides representing the binding epitopes of N- and C-termini were measured by means of fluorescence anisotropy (FA). The importance of representative basic amino acids and their combinations from both peptides for the binding of endogenous TRPM4 modulators was proved using point alanine-scanning mutagenesis. In silico protein-protein docking of both peptides to CaM and S100A1 and extensive molecular dynamics (MD) simulations enabled the description of key stabilising interactions at the atomic level. Recently solved cryo-Electron Microscopy (EM) structures made it possible to put our findings into the context of the entire TRPM4 channel and to deduce how the binding of these endogenous modulators could allosterically affect the gating of TRPM4. Moreover, both identified binding epitopes seem to be ideally positioned to mediate the involvement of TRPM4 in higher-order hetero-multimeric complexes with important physiological functions.
Keywords: kinetika; Calmodulin; interakční proteinové domény a motivy; kalmodulin; Kinetics; fluorescence anisotropy; Protein Interaction Domains and Motifs; vazebná místa; TRPM4 channel; binding epitope; sekvence aminokyselin; CaM; TRPM Cation Channels; vazba proteinů; Structure-Activity Relationship; S100 Proteins; lidé; molecular dynamics simulations; kationtové kanály TRPM; PIP2; Amino Acid Sequence; akvaporiny; peptidové fragmenty; Models, Molecular; Humans; Protein Conformation; molekulární modely; Peptide Fragments; Multiprotein Complexes; konformace proteinů; vztahy mezi strukturou a aktivitou; docking; S100A1; proteiny S100; Protein Binding; Aquaporins; Binding Sites; multiproteinové komplexy